2003
DOI: 10.1093/brain/awg050
|View full text |Cite
|
Sign up to set email alerts
|

Gluten ataxia in perspective: epidemiology, genetic susceptibility and clinical characteristics

Abstract: We previously have described a group of patients with gluten sensitivity presenting with ataxia (gluten ataxia) and suggested that this disease entity may account for a large number of patients with sporadic idiopathic ataxia. We have therefore investigated the prevalence of gluten sensitivity amongst a large cohort of patients with sporadic and familial ataxia and looked at possible genetic predisposition to gluten sensitivity amongst these groups. Two hundred and twenty-four patients with various causes of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
175
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(186 citation statements)
references
References 19 publications
5
175
2
4
Order By: Relevance
“…Also it considered a good source of traces minerals like selenium and magnesium, nutrients essential to wound healing. Hadjivassiliou 2003 concluded that wholewheat grain supplies elements needed by the human body as Starch and gluten which provide heat and energy; phosphates and other mineral salts, vitamins B and E and protein that help in building and repairing of muscular tissue (52)(53)(54)(55)(56)(57) .As regard the relation between macro, micronutrient and hemoglobin level, serum albumin and total protein the present study illustrated that there was a positive significant relation between dietary protein intake and hemoglobin level, serum albumin and total protein. Due stated that heme iron absorption is less affected by substances in the diet than non-heme iron, indicating that heme iron absorption is determined mainly by the body iron levels and, to a very minor extent, by dietary factors (58)(59)(60)(61)(62)(63) .…”
Section: Effect Of Therapeutic Dietary Regimen On Wound Healing For Psupporting
confidence: 54%
“…Also it considered a good source of traces minerals like selenium and magnesium, nutrients essential to wound healing. Hadjivassiliou 2003 concluded that wholewheat grain supplies elements needed by the human body as Starch and gluten which provide heat and energy; phosphates and other mineral salts, vitamins B and E and protein that help in building and repairing of muscular tissue (52)(53)(54)(55)(56)(57) .As regard the relation between macro, micronutrient and hemoglobin level, serum albumin and total protein the present study illustrated that there was a positive significant relation between dietary protein intake and hemoglobin level, serum albumin and total protein. Due stated that heme iron absorption is less affected by substances in the diet than non-heme iron, indicating that heme iron absorption is determined mainly by the body iron levels and, to a very minor extent, by dietary factors (58)(59)(60)(61)(62)(63) .…”
Section: Effect Of Therapeutic Dietary Regimen On Wound Healing For Psupporting
confidence: 54%
“…nystagmus were reported most frequently. [56] Anti-gliadin antibodies cross-reacting with epitopes on cerebellar Purkinje fibers is suggested by the authors as the likely mechanism. Whether gluten ataxia exists in the absence of celiac disease is controversial.…”
Section: Neurological Manifestationsmentioning
confidence: 96%
“…Gluten ataxia is considered a distinct disease process which can occur with or without enteropathy and is associated with high anti-gliadin antibody titers. [56] Hadjivassiliou et al demonstrated a 32% prevalence of anti-gliadin antibodies among patients with sporadic idiopathic ataxia. 24% of this gluten ataxia group had evidence of gluten-sensitive enteropathy and only 13% reported gastrointestinal symptoms.…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…Clinical features include ocular signs of cerebellar dysfunction such as gaze evoked nystagmus in over 80% of cases, upper or lower limb ataxia, gait ataxia, and dysarthria [37,40,41]. MRI findings indicate atrophy of the cerebellum and white matter hyperintensities [40].…”
Section: Ataxiamentioning
confidence: 99%
“…Clinical features include ocular signs of cerebellar dysfunction such as gaze evoked nystagmus in over 80% of cases, upper or lower limb ataxia, gait ataxia, and dysarthria [37,40,41]. MRI findings indicate atrophy of the cerebellum and white matter hyperintensities [40]. Hadjivassiliou et al [42] reported finding prevalent deposits of anti-tissue transglutaminase IgA antibodies in the brain, most notably in the medulla, pons and cerebellum.…”
Section: Ataxiamentioning
confidence: 99%